PERENCANAAN DAN PENGELOLAAN BADAN USAHA MILIK DESA (BUMDES) DALAM MENINGKATKAN PENDAPATAN ASLI DESA DI KECAMATAN PAHAE JAE KABUPATEN TAPANULI UTARA - Hamonangan Siallagan; Rizki Christian Sipayung (LPPM Universitas Bina Bangsa, 2023)
The purpose of the activities of dedication to this community is to provide training on how to make planning and management of the Village Ownership Enterprise Agency (BUMDes) in increasing the original income of the village in the Pahae Jae district of Tapanuli North. Understand the importance of using good strategies in managing BUMDes. BUMDes managers should be able to think creatively in creating a business. And the effort that was created was not the same effort that had been initiated by other villagers so that BUMDes did not kill the community’s efforts that were already out there. Therefore, it is important to carry out mature funding and good management of BUMDes so that the results of the BUMDES can increase the well-being of the villagers and also increase the natural income of the village. (PADes). The result of this dedication activity is that the managers of BUMDes, the head of the village, and the village assistant can understand how to manage the bUMDes in the village so that they can increase the village income in the Pahae Jae district of Tapanuli North